Group VII Ethylene Response Factors Coordinate Oxygen and Nitric Oxide Signal Transduction and Stress Responses in Plants - Gibbs, Daniel J. (Plant Physiol, 2015)
The group VII ethylene response factors (ERFVIIs) are plant-specific transcription factors that have emerged as important regulators of abiotic and biotic stress responses, in particular, low-oxygen stress. A defining feature of ERFVIIs is their conserved N-terminal domain, which renders them oxygen- and nitric oxide (NO)-dependent substrates of the N-end rule pathway of targeted proteolysis. In the presence of these gases, ERFVIIs are destabilized, whereas an absence of either permits their accumulation; ERFVIIs therefore coordinate plant homeostatic responses to oxygen availability and control a wide range of NO-mediated processes. ERFVIIs have a variety of context-specific protein and gene interaction partners, and also modulate gibberellin and abscisic acid signaling to regulate diverse developmental processes and stress responses. This update discusses recent advances in our understanding of ERFVII regulation and function, highlighting their role as central regulators of gaseous signal transduction at the interface of ethylene, oxygen, and NO signaling.